Decorative sheet

By using a surface protective layer of a specific concave and convex structure and an ionizing radiation curable resin on the decorative sheet, combining particles and pattern layers, the balance problem of the decorative sheet between low gloss and high pollution resistance is solved, achieving a wet touch and excellent Durability.

CN119317538APending Publication Date: 2025-01-14TOPPAN HOLDINGS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044997.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-06-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing decorative sheets have difficulty finding a balance between design and durability, especially in terms of low gloss and high stain resistance, and are difficult to achieve a wet touch.

Method used

Using a surface protective layer with a specific concave and convex structure and resin curing product, combined with the use of ionizing radiation curable resin and particles, a surface protective layer with a thickness of more than 2 μm and less than 18 μm is formed to ensure that the gloss is less than 10, and to protect the raw material layer and surface. Add pattern layers between layers to enhance design.

Benefits of technology

It realizes the wet touch of the decorative sheet, improves pollution resistance and damage resistance, while maintaining low gloss and excellent processability, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317538A_ABST
    Figure CN119317538A_ABST
Patent Text Reader

Abstract

A decorative sheet (1) is provided with a raw material layer (2) and a surface protection layer (5) provided on one surface of the raw material layer (2), and the surface of the surface protection layer (5) is provided with an uneven structure including a plurality of ridge-shaped portions each protruding in a ridge shape. The ratio (Rdc / t) of the cross-sectional height difference (Rdc) of the uneven structure of the surface protection layer (5) to the thickness t of the surface protection layer (5) is 0.1-0.2, the thickness t of the surface protection layer (5) is 2-18 [mu] m, the surface protection layer (5) contains a cured product of a resin and particles, the average particle diameter of the particles is 3 [mu] m or more, and the average particle diameter of the particles is 3 [mu] m or more. The particles are contained in the surface protective layer (5) in an amount of 3-11 parts by mass (inclusive) per 100 parts by mass of the resin, and the surface protective layer (5) has a glossiness of less than 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a decorative sheet. Background Art

[0002] Decorative sheets are used for surface decoration of interior and exterior materials such as doors and windows, furniture, building materials, and floor materials to give these parts design and durability. Decorative sheets are generally pasted on the surface of substrates such as wood, wooden boards, metal plates, non-combustible boards, paper substrates, and resin substrates with adhesives to form decorative panels, and are widely used.

[0003] Design is imparted by, for example, using various printing methods to form patterns such as wood grain or stone grain. A plain color without a pattern is also preferred for the decorative sheet in some cases. Whether or not there is a pattern and the type of pattern vary depending on the application and preference.

[0004] The glossiness of the surface is also important for the design of the decorative sheet. As decorative sheets, various choices can be made, ranging from high gloss like a mirror surface to low gloss without any reflection, depending on the application and preference.

[0005] In addition, as mentioned above, as a function of the decorative sheet that is equally important as imparting design, imparting durability can be cited. Durability refers to a comprehensive evaluation of scratch resistance and stain resistance, and whether these properties can be ensured continuously for a long time. The requirements vary depending on the environment and conditions in which the decorative sheet is used, but a decorative sheet with high performance is always required.

[0006] In order to impart durability, a surface protection layer is generally formed on the outermost surface of the decorative sheet. In addition, in order to adjust the glossiness, especially to achieve low glossiness, a gloss adjuster (matt additive) is generally added to the surface protection layer.

[0007] Furthermore, since the decorative sheet is generally subjected to processing such as cutting and bending in order to form a decorative material such as a decorative plate, it is preferable that the decorative sheet has processability that can withstand such processing.

[0008] As described above, as a decorative sheet that takes design properties (low gloss), scratch resistance, and stain resistance into consideration, there is a decorative sheet described in Patent Document 1, for example.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2019-119138 Summary of the invention

[0012] Problems to be solved by the invention

[0013] An object of the present invention is to provide a decorative sheet that imparts a moist touch.

[0014] Means for solving problems

[0015] According to one aspect of the present invention, there is provided a decorative sheet comprising a raw material layer and a surface protective layer arranged on a surface of the raw material layer, wherein a concave-convex structure comprising a plurality of ridge-shaped portions each protruding in a ridge shape is arranged on the surface of the surface protective layer, a ratio Rdc / t of a cross-sectional height difference Rdc of the concave-convex structure of the surface protective layer to a thickness t of the surface protective layer is greater than or equal to 0.1 and less than or equal to 0.2, a thickness t of the surface protective layer is greater than or equal to 2 μm and less than or equal to 18 μm, the surface protective layer contains a cured product of a resin and particles, the average particle size of the particles is greater than or equal to 3 μm, the particles are contained in the surface protective layer in an amount of greater than or equal to 3 parts by mass and less than or equal to 11 parts by mass relative to 100 parts by mass of the resin, and the glossiness of the surface protective layer is less than 10.

[0016] According to another aspect of the present invention, there is provided the decorative sheet according to the above aspect, wherein the average particle size of the particles is not less than 3 μm and not more than 11 μm.

[0017] According to still another aspect of the present invention, there is provided the decorative sheet according to any one of the above aspects, wherein the resin is an ionizing radiation curable resin.

[0018] According to yet another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the resin is acrylate.

[0019] According to still another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the resin is a trifunctional acrylate having a repeating structure, and the repeating number of the repeating structure is 3 to 20.

[0020] According to still another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein the resin is a tetrafunctional acrylate having a repeating structure, and the repeating number of the repeating structure is 20 to 35.

[0021] According to still another aspect of the present invention, there is provided a decorative sheet according to any one of the above aspects, wherein a pattern layer is further provided between the raw material layer and the surface protection layer.

[0022] According to still another aspect of the present invention, there is provided a decorative material comprising: the decorative sheet according to any one of the above aspects, and a base material to which the decorative sheet is attached.

[0023] Effects of the Invention

[0024] According to the present invention, a decorative sheet imparting a moist touch can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] [ Figure 1 ] Figure 1 This is a cross-sectional view of a decorative material including a decorative sheet according to one embodiment of the present invention.

[0026] [ Figure 2 ] Figure 2 yes Figure 1 A cross-sectional view of a surface protective layer included in a decorative sheet.

[0027] [ Figure 3 ] Figure 3 This is a microscope image of a surface protection layer included in a decorative sheet according to an example of the present invention. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The embodiments described below are embodiments that further specify any of the above aspects. The matters described below may be incorporated into the above aspects individually or in combination.

[0029] In addition, the embodiments shown below illustrate the configuration for embodying the technical concept of the present invention, and the technical concept of the present invention is not limited by the material, shape, and structure of the following components. The technical concept of the present invention can be variously modified within the technical scope specified by the claims described in the claims.

[0030] It should be noted that, for elements having the same or similar functions, the same reference symbols are marked in the drawings referred to below, and repeated descriptions are omitted. In addition, the drawings are schematic, and the relationship between the dimensions in a certain direction and the dimensions in other directions, and the relationship between the dimensions of a certain component and the dimensions of other components, etc. may be different from the actual situation.

[0031] <1> Decorative materials and decorative sheets

[0032] Figure 1 This is a cross-sectional view of a decorative material including a decorative sheet according to one embodiment of the present invention. Figure 2 yes Figure 1 A cross-sectional view of a surface protective layer included in a decorative sheet. Figure 3 This is a microscopic photograph of a surface protection layer included in a decorative sheet according to an example of the present invention.

[0033] It should be noted that Figure 2 The cross section shown is a cross section along the thickness direction of the surface protection layer. Figure 3 The microscopic photographs are plane photographs obtained using a laser microscope (OLS-4000 manufactured by Olympus Corporation).

[0034] Figure 1 The decorative material 11 shown includes a substrate B and a decorative sheet 1 attached thereto. Here, the decorative material 11 is a decorative board. The decorative board can be flat, curved or folded. The decorative material 11 can also have a shape other than a board.

[0035] Here, the substrate B is a plate. The plate is, for example, a wooden plate, an inorganic plate, a metal plate, or a composite plate composed of a plurality of materials. The substrate B may have a shape other than a plate.

[0036] The decorative sheet 1 includes a raw material layer 2, a pattern layer 3, a transparent resin layer 4, a surface protection layer 5, an adhesive layer 7, a primer layer 6, and a concealing layer 8. The pattern layer 3, the adhesive layer 7, the transparent resin layer 4, and the surface protection layer 5 are sequentially arranged on the surface of the raw material layer 2 opposite to the surface facing the substrate B from the raw material layer 2 side. The concealing layer 8 and the primer layer 6 are sequentially arranged on the surface of the raw material layer 2 facing the substrate B from the raw material layer 2 side. One or more of the pattern layer 3, the transparent resin layer 4, the primer layer 6, the adhesive layer 7, and the concealing layer 8 may be omitted. The elements included in the decorative sheet 1 are described in sequence below.

[0037] <1.1> Raw material layer

[0038] As the raw material layer 2 or its material, for example, a material selected arbitrarily from paper, synthetic resin, synthetic resin foam, rubber, non-woven fabric, synthetic paper, metal foil, etc. can be used. As paper, thin leaf paper, titanium paper, resin-impregnated paper, etc. can be exemplified. As synthetic resin, polyethylene, polypropylene, polybutene, polystyrene, polycarbonate, polyester, polyamide, ethylene-vinyl acetate copolymer, polyvinyl alcohol, acrylic acid, etc. can be exemplified. As rubber, ethylene-propylene copolymer rubber, ethylene-propylene-diene copolymer rubber, styrene-butadiene copolymer rubber, styrene-isoprene-styrene block copolymer rubber, styrene-butadiene-styrene block copolymer rubber, polyurethane, etc. can be exemplified. As non-woven fabric, organic or inorganic non-woven fabric can be used. As the metal of the metal foil, aluminum, iron, gold, silver, etc. can be exemplified.

[0039] Taking printing workability, cost, and the like into consideration, the thickness of the original material layer 2 is preferably within a range of 20 μm to 250 μm.

[0040] <1.2> Primer layer

[0041] When an olefin resin is used as the material of the raw material layer 2, the surface of the raw material layer 2 is often in an inert state. Therefore, in this case, it is preferred to provide a primer layer 6 between the raw material layer 2 and the substrate B. When the raw material layer 2 is composed of an olefin material, in order to omit the primer layer 6 and improve the adhesion between the raw material layer 2 and the substrate B, the raw material layer 2 may be subjected to a surface modification treatment such as a corona treatment, a plasma treatment, an ozone treatment, an electron beam treatment, an ultraviolet treatment, a dichromic acid treatment, etc.

[0042] As the material of the primer layer 6, for example, the material of the pattern layer 3 described later can be used. Since the primer layer 6 is applied to the back side of the decorative sheet 1, when the decorative sheet 1 is wound in a web shape, in order to avoid sticking and improve the adhesion with the adhesive, an inorganic filler can be added to the primer layer 6. Examples of the inorganic filler include silicon dioxide, aluminum oxide, magnesium oxide, titanium oxide, barium sulfate, and the like.

[0043] <1.3> Hidden layer

[0044] In order to provide concealment to the base material B in the decorative sheet 1, for example, a colored sheet can be used as the raw material layer 2 or an opaque concealing layer 8 can be provided. The concealing layer 8 can be made of the same material as the pattern layer 3 described later. However, since the concealing layer 8 is intended for concealment, it is preferred to use an opaque pigment, titanium oxide, iron oxide, etc. as the pigment. In addition, in order to improve concealment, for example, metals such as gold, silver, copper, and aluminum can be added to the material of the concealing layer 8. Usually, thin aluminum sheets are added.

[0045] <1.4> Pattern layer

[0046] The pattern layer 3 is a layer formed by printing a pattern on the raw material layer 2 using ink. As a binder for the ink, for example, nitrocellulose, cellulose, vinyl chloride-vinyl acetate copolymer, polyvinyl butyral, polyurethane, acrylic, polyester, or their modified products can be used alone or in combination. The binder can be any of aqueous, solvent-based, and emulsion-based, and can be a one-component type or a two-component type using a curing agent. The pattern layer 3 can be formed by a method of curing a layer formed by curable ink by irradiation with ultraviolet rays or electron beams. Among them, the most common method is a method of using a carbamate-based ink and curing it with an isocyanate. In addition to the binder, the ink used to form the pattern layer 3 can also contain colorants such as pigments and dyes contained in ordinary inks, body pigments, solvents, various additives, etc. As pigments with high versatility, for example, pearl pigments such as condensed azo, insoluble azo, quinacridone, isoindoline, anthraquinone, imidazolones, cobalt, phthalocyanine, carbon, titanium oxide, iron oxide, and mica can be listed.

[0047] In addition to the application of ink, the pattern layer 3 can also be designed by evaporation or sputtering of various metals. In particular, it is preferred to add a light stabilizer to the ink. This can suppress the deterioration of the decorative sheet 1 itself caused by light deterioration of the ink and extend the life of the decorative sheet 1.

[0048] <1.5> Adhesive layer

[0049] The adhesive layer 7 is also called a heat-sensitive adhesive layer, an anchor coating layer, or a dry lamination adhesive layer.

[0050] The resin material of the adhesive layer 7 is not particularly limited, for example, it can be appropriately selected and used from resin materials such as acrylic acid, polyester, polyurethane, epoxy, etc. In addition, as the resin material of the adhesive layer 7, for example, ethylene-vinyl acetate copolymer resin adhesive can also be used. The coating method can be appropriately selected according to the viscosity of the adhesive, etc. Usually a gravure coater is used, and after the gravure coater is used to form the adhesive layer 7 on the pattern layer 3, the transparent resin layer 4 is laminated. It should be noted that, when the bonding strength between the transparent resin layer 4 and the pattern layer 3 is fully obtained, the adhesive layer 7 can be omitted.

[0051] <1.6> Transparent resin layer

[0052] As the resin material of the transparent resin layer 4, an olefin resin is preferably used. As the olefin resin, for example, in addition to polypropylene, polyethylene, polybutene, etc., alpha olefins (for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1 1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, etc.) or copolymers of two or more thereof; copolymers obtained by copolymerizing ethylene or α-olefins with monomers other than these, such as ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-methyl methacrylate copolymers, ethylene-ethyl methacrylate copolymers, ethylene-butyl methacrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, etc.

[0053] In addition, in order to improve the surface strength of the decorative sheet 1, highly crystalline polypropylene is preferably used as the resin of the transparent resin layer 4. It should be noted that various additives such as (for example) heat stabilizers, light stabilizers, anti-blocking agents, catalyst scavengers, colorants, light scattering agents, and gloss regulators may be added to the transparent resin layer 4 as needed. As heat stabilizers, phenolic, sulfur, phosphorus, hydrazine, etc. are generally added in any combination, and as light stabilizers, hindered amines, etc. are generally added in any combination.

[0054] <1.7> Surface protection layer

[0055] The surface protection layer 5 includes a core portion 5A and a plurality of ridge portions 5B each protruding in a ridge shape from one surface of the core portion 5A. These ridge portions 5B form a concavo-convex structure.

[0056] Here, in the decorative sheet 1 involved in the present embodiment, "ridge-shaped" refers to a convex shape that is linear in a plan view. The shape of the ridge portion 5B in a plan view may be curved or linear, but from the perspective of the anti-fingerprint property of the decorative sheet 1, a curved shape is preferred. Each of the ridge portions 5B may be branched or unbranched in a plan view. In addition, in the present disclosure, the ridge portion 5B is, for example, a portion from the lowest portion to the top of the concave-convex shape provided on the surface of the surface protection layer 5, and the core portion 5A refers to the portion of the surface protection layer 5 other than the ridge portion 5B.

[0057] For example, Figure 3 As shown, the ridge portions 5B are each curved, and at least a portion thereof is adjacent to each other in the width direction. At a position where at least a portion of the ridge portions 5B is adjacent to each other in the width direction, a cross section of the surface protection layer 5 parallel to the width direction and the thickness direction of the surface protection layer 5 is as shown in FIG. Figure 2 As shown, the portion provided with the concavo-convex structure has a wave shape such as a sine wave shape.

[0058] The ratio Rdc / t of the cross-sectional height difference Rdc of the concavo-convex structure of the surface protection layer 5 to the thickness t of the surface protection layer 5 (hereinafter also simply referred to as "ratio Rdc / t") is 0.1 to 0.2. The ratio Rdc / t is preferably 0.11 to 0.19.

[0059] "Cross-sectional height difference Rdc" is a surface property parameter specified in JIS B0601:2013. The cross-sectional height difference Rdc indicates the cross-sectional height difference of the roughness curve, and expresses the steepness of the concave-convex shape. Here, the highest peak position of the roughness curve is set as the reference for the cross-sectional height c. In addition, here, c(Rmr1) is set as the cross-sectional height when the load length ratio Rmr of the roughness curve is 10%, and c(Rmr2) is set as the cross-sectional height when the load length ratio Rmr of the roughness curve is 25%. The cross-sectional height difference Rdc (μm) of the roughness curve is the difference between the cross-sectional height c(Rmr1) and the cross-sectional height c(Rmr2). When the cross-sectional height difference Rdc is divided by the thickness t of the surface protection layer 5 to obtain the ratio Rdc / t, the steepness of the concave-convex shape per unit thickness of the surface protection layer 5 can be expressed.

[0060] It should be noted that the area on the surface of the surface protection layer corresponding to the portion of the roughness curve where the load length ratio Rmr is less than 10% is the area that the fingertip first contacts when the surface protection layer is pressed by the fingertip. The area on the surface of the surface protection layer where the fingertip first contacts the surface protection layer when the surface protection layer is pressed by the fingertip has a small effect on the wet touch. In addition, the area on the surface of the surface protection layer where the fingertip first contacts when the pressure applied from the fingertip to the surface protection layer is extremely large also has a small effect on the wet touch. The inclination of the area on the surface of the surface protection layer where the fingertip first contacts when the pressure applied from the fingertip to the surface protection layer increases to a certain extent has a great effect on the wet touch. This area corresponds to the area corresponding to the portion of the roughness curve where the load length ratio Rmr is in the range of 10% to 25%.

[0061] When the value of the ratio Rdc / t is 0.1 or more and 0.2 or less, the slope of the concavo-convex shape is relatively gentle. In this case, when the surface of the decorative sheet is pressed with a finger and the finger is slid on the surface, the indentation resistance caused by the contact between the finger and the surface is small, and the contact area between the finger and the convex surface gradually increases, so that the surface of the decorative sheet is attached to the finger. This touch can correspond to a "wet touch".

[0062] On the other hand, when the ratio Rdc / t is greater than 0.2, the slope of the concavoconvex shape becomes steep. In this case, when the surface of the decorative sheet is pressed with a finger and the finger is slid on the surface, the indentation resistance caused by the contact between the finger and the surface is large, and the presence of the concavoconvex shape can be felt. This tactile feeling can be corresponded to a "rough tactile feeling".

[0063] In addition, when the ratio Rdc / t is less than 0.1, the slope of the concavo-convex shape is quite gentle. In this case, when the surface of the decorative sheet is pressed with a finger while the finger is slid on the surface, the indentation resistance caused by the contact between the finger and the surface is small, and the contact area between the finger and the convex surface is large from the beginning of the pressing action, and the increase of the contact area with the pressing action is quite slow. Therefore, in this case, the tactile feeling of the surface of the decorative sheet adsorbed on the finger is obtained, and on the other hand, the slope of the concavo-convex shape is quite gentle, and compared with the above-mentioned "wet touch", a good sliding touch is obtained, and as a whole, the impression of the good sliding touch is enhanced. This touch can correspond to a "smooth touch".

[0064] The thickness t of the surface protection layer 5 is not less than 2 μm and not more than 18 μm. The thickness t of the surface protection layer 5 is preferably not less than 3 μm and not more than 10 μm. When the thickness of the surface protection layer 5 is increased, a tendency for the value of the ratio Rdc / t to become larger can be seen. Therefore, when the thickness of the surface protection layer 5 is too small or too large, it is difficult to achieve a "wet touch". In addition, when the thickness of the surface protection layer 5 is reduced, it is difficult to achieve low gloss. Here, the thickness of the surface protection layer 5 is obtained by observing the cross section using a scanning electron microscope and averaging 25 points. Specifically, the thickness of the surface protection layer 5 can be obtained as described in the embodiments described later. It should be noted that, in the case where the surface protection layer coating liquid described later does not contain a solvent, the thickness of the coating film formed by the surface protection layer coating liquid is equal to the thickness of the surface protection layer 5.

[0065] The surface protective layer 5 contains a cured product of a resin and particles.

[0066] The resin contained in the surface protection layer 5 is preferably an ionizing radiation curable resin. Here, "ionizing radiation" is a charged particle beam such as an electron beam. The ionizing radiation curable resin is cured by irradiation with ionizing radiation. In addition, the ionizing radiation curable resin can also be cured by ultraviolet irradiation. The ionizing radiation curable resin used here is cured by irradiation with light having a wavelength of less than 200nm, and on the other hand, has a large absorption coefficient for the light.

[0067] The amount of the cured product of the ionizing radiation curable resin in the surface protection layer 5 is preferably 60% by mass or more, more preferably 70% by mass or more, and further preferably 80% by mass or more. As the ionizing radiation curable resin, various monomers or commercially available oligomers and other known resins can be used, for example, (meth) acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, epoxy resins can be used. The ionizing radiation curable resin can be any of an aqueous resin or a non-aqueous (organic solvent) resin.

[0068] The main component of the ionizing radiation curable resin is preferably an acrylate. Here, the main component of the ionizing radiation curable resin refers to a component that accounts for 60% by mass or more in the ionizing radiation curable resin. The ionizing radiation curable resin preferably contains acrylate in an amount of 70 parts by mass or more, and more preferably contains acrylate in an amount of 80 parts by mass or more. The ionizing radiation curable resin is more preferably an acrylate.

[0069] The acrylate is preferably a difunctional or higher acrylate, more preferably a trifunctional or higher acrylate. In order to obtain a surface protection layer 5 having excellent scratch resistance, the acrylate is preferably trifunctional or higher. There is no upper limit to the number of functional groups of the acrylate, but according to one example, it is hexafunctional or lower.

[0070] The acrylate preferably contains a repeating structure. The repeating structure is, for example, any one of an ethylene oxide (EO) structure, a propylene oxide (PO) structure, and an ε-caprolactone (CL) structure. The repeating structure is preferably ethylene oxide or propylene oxide. In the acrylate, the repeating structure may be between an acryloyl group and a hydroxymethyl group in an open ring state.

[0071] The number of repetitions of the repeating structure is preferably 3 or more. When an acrylic acid ester having a large number of repetitions is used, the cured film is likely to expand in the in-plane direction in the first irradiation step described later, and therefore wrinkles corresponding to the ridge 5B are likely to be generated on the coating surface. In addition, when an acrylic acid ester having a large number of repetitions is used, a tendency for the value of the ratio Rdc / t to become larger can be seen. However, when the number of repetitions is increased, the crosslinking density decreases, and the scratch resistance of the surface protective layer decreases.

[0072] In a preferred embodiment, the ionizing radiation curable resin is a trifunctional acrylate containing a repeating structure. The trifunctional acrylate containing a repeating structure is, for example, EO-modified, PO-modified or CL-modified trimethylolpropane triacrylate, glycerol triacrylate, isocyanurate triacrylate, or pentaerythritol triacrylate. In the trifunctional acrylate containing a repeating structure, the number of repetitions of the repeating structure is preferably 3 or more, more preferably 3 or more and 30 or less, and further preferably 3 or more and 20 or less.

[0073] In another preferred embodiment, the ionizing radiation curable resin is a tetrafunctional acrylate containing a repeating structure. The tetrafunctional acrylate containing a repeating structure is, for example, EO-modified, PO-modified or CL-modified pentaerythritol tetraacrylate. In the tetrafunctional acrylate containing a repeating structure, the number of repetitions of the repeating structure is preferably 12 or more, more preferably 12 or more and 50 or less, further preferably 20 or more and 50 or less, and further preferably 20 or more and 35 or less.

[0074] The number of repetitions of the above-mentioned repeating structure can be analyzed using MALDI-TOF-MS. The ionizing radiation curable resin may have a molecular weight distribution. In the case of having a molecular weight distribution, the number of repetitions is set to the number of repetitions corresponding to the molecular weight having the strongest peak in the MALDI-TOF-MS mass spectrum.

[0075] As particles contained in the surface protection layer 5, for example, particles composed of organic materials such as polyethylene (PE) wax, polypropylene (PP) wax, and resin beads; or particles composed of inorganic materials such as silica, glass, alumina, titanium dioxide, zirconium oxide, calcium carbonate, and barium sulfate can be used.

[0076] The average particle size (D50) of the particles is 3 μm or more. The average particle size (D50) of the particles is preferably 3 μm or more and 11 μm or less, and more preferably 4 μm or more and 10 μm or less.

[0077] When the surface protection layer 5 contains particles, wrinkles can be generated more uniformly on the surface of the coating film in the first irradiation step described later. When the average particle size (D50) of the particles increases, a tendency to decrease in the value of the ratio Rdc / t can be seen. Therefore, when the average particle size (D50) is too small or too large, it is difficult to achieve a "wet touch". In addition, when large particles are used, the particles are sometimes easy to fall off from the surface protection layer 5, making it difficult to achieve high scratch resistance. When the particles are small, the effect of uniformly generating wrinkles is small.

[0078] Here, "average particle size (D50)" is the median particle size (D50) measured by a laser diffraction / scattering particle size distribution measuring device. It should be noted that, when the surface protection layer coating liquid contains particles, the surface protection layer 5 obtained from the coating liquid also contains particles. The average particle size of the particles contained in the surface protection layer 5 can be a value obtained by observing its cross section, measuring the particle size of multiple particles and averaging them. The value obtained in this way is substantially the same as the median particle size (D50) measured by a laser diffraction / scattering particle size distribution measuring device. Therefore, the range of the above-mentioned average particle size can also be read as the range of the average particle size of the particles contained in the surface protection layer 5.

[0079] The particles are contained in the surface protection layer 5 in an amount of 3 parts by mass or more and 11 parts by mass or less relative to 100 parts by mass of the resin. The amount of particles added is preferably 4 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the resin. It should be noted that "100 parts by mass of the resin" refers to the mass parts of the solid content of the resin.

[0080] When the amount of particles added is within the above range, the effect of uniformly generating wrinkles is particularly large. When the amount of particles added is large, a tendency of a decrease in the value of the ratio Rdc / t can be seen. Therefore, when the amount of particles added is too small or too large, it is difficult to achieve a "wet touch". In addition, when the amount of particles added is large, the particles are sometimes easy to fall off from the surface protection layer 5, making it difficult to achieve high scratch resistance. When the amount of particles added is small, the effect of uniformly generating wrinkles is small.

[0081] The glossiness of the surface protection layer 5 is less than 10.0. The glossiness of the surface protection layer 5 is preferably 5 or less. Here, the "glossiness" is a measured value when measured at an incident angle of 60 degrees using a gloss meter in accordance with JIS Z8741:1997.

[0082] <2> Method for manufacturing decorative sheet

[0083] The decorative sheet 1 is produced, for example, by the following method. Here, for simplicity, the description of the pattern layer 3, the transparent resin layer 4, the primer layer 6, the adhesive layer 7, and the concealing layer 8 is omitted.

[0084] First, a coating film composed of a coating liquid for a surface protective layer is formed on one surface of the raw material layer 2. The coating film can be formed by various printing methods such as gravure printing, offset printing, screen printing, electrostatic printing, and inkjet printing; or various coating methods such as roll coating, blade coating, micro gravure coating, and die coating.

[0085] The coating liquid for the surface protection layer contains the above-mentioned resin and the above-mentioned particles. The coating liquid for the surface protection layer may also contain a solvent or an additive (such as an antibacterial agent and a mildewproof agent) for improving the function of the final product. The coating liquid for the surface protection layer may also contain other additives such as ultraviolet absorbers and light stabilizers. As ultraviolet absorbers, for example, benzotriazole series, benzoate series, benzophenone series, triazine series, etc. can be used. As light stabilizers, for example, hindered amine series, etc. can be used. It should be noted that according to the method described here, a surface protection layer 5 with low gloss can be formed without a gloss regulator (matting additive).

[0086] In the second irradiation step described later, when the coating film composed of the surface protection layer coating liquid is cured as a whole by ultraviolet irradiation, the surface protection layer coating liquid preferably further contains a photoinitiator. The photoinitiator is not particularly limited, and examples thereof include benzophenone-based, acetophenone-based, benzoin ether-based, and thioxanthone-based photoinitiators.

[0087] After forming a coating film composed of a coating liquid for a surface protection layer, the first irradiation process is implemented. In the first irradiation process, light with a wavelength of less than 200nm (hereinafter referred to as the first radiation) is irradiated to the coating film. The ionizing radiation curable resin contained in the coating liquid for the surface protection layer has a large absorption coefficient for the first radiation. Therefore, the first radiation incident on the coating film can only reach a position with a distance of tens to hundreds of nm from its outermost surface. Therefore, in the first irradiation process, a cross-linking reaction is carried out in the surface area of ​​the coating film to form an extremely thin cured film, and on the other hand, a cross-linking reaction is not carried out in other areas and remains uncured.

[0088] The coating film after the first irradiation step has wrinkles on the surface corresponding to the ridge-shaped portions 5B. The present inventors believe that the reason why wrinkles are generated on the coating film surface by the first irradiation step is as follows.

[0089] As mentioned above, the first radiation can only reach a position where the distance from the outermost surface of the coating film is tens to hundreds of nm. That is, the cross-linking reaction of the ionizing radiation curable resin occurs only on the surface of the coating film, and the region closer to the innermost surface than tens to hundreds of nm is not solidified, and there are molecules with high fluidity. Such molecules with high fluidity increase the volume of the cured film by swelling the cured film. Relative to the in-plane compressive stress generated by the volume increase in the in-plane direction, the cured film is buckled, thereby producing a wrinkled shape on the coating film surface.

[0090] The first radiation can be extracted from excimer VUV (Vacuum Ultra Violet) light. Excimer VUV light can be generated by a lamp using a rare gas or a rare gas halide. When high-energy electrons are applied from the outside to a lamp that encloses a rare gas or a rare gas halide gas, a large amount of discharge plasma (dielectric barrier discharge) is generated. Through this plasma discharge, the atoms of the discharge gas (rare gas) are excited and instantly become a quasi-molecular state. When returning to the ground state from the quasi-molecular state, light in a wavelength region unique to the quasi-molecule is emitted.

[0091] The gas used for the excimer lamp can be any gas used in the past as long as it emits light below 200nm. As the gas, rare gases such as Xe, Ar, and Kr, and mixed gases of rare gases such as ArBr and ArF and halogen gases can be used. The wavelength (center wavelength) of the excimer lamp varies depending on the gas, for example, it has a wavelength of about 172nm (Xe), about 126nm (Ar), about 146nm (Kr), about 165nm (ArBr), about 193nm (ArF), etc.

[0092] Considering the difference between the size of photon energy, wavelength and the binding energy of organic matter, it is preferred to use a xenon lamp that emits excimer light with a central wavelength of 172nm as a light source. In addition, if the cost of equipment maintenance and the acquisition of materials are also considered, it is preferred to use a xenon lamp as a light source.

[0093] The first irradiation step is performed in an atmosphere with a low oxygen concentration. Oxygen has a large absorption coefficient for light below 200 nm. Therefore, the first irradiation step is preferably performed in a nitrogen atmosphere, for example. The oxygen concentration in the gas phase of the first irradiation step, that is, the residual oxygen concentration in the reaction atmosphere is preferably set to 2000 ppm or less, and more preferably set to 1000 ppm or less.

[0094] In addition, oxygen in the atmosphere inhibits free radical polymerization. Therefore, the residual oxygen concentration in the reaction atmosphere affects the formation of wrinkles on the coating surface. Therefore, when the residual oxygen concentration in the reaction atmosphere changes, the surface properties of the surface protection layer 5 may also change.

[0095] The integrated light intensity of the first radiation is preferably set to 0.5 mJ / cm 2 Above 200mJ / cm 2 Below, more preferably 1 mJ / cm 2 Above 100mJ / cm 2 Below, more preferably set to 3mJ / cm 2 Above 50mJ / cm 2 Below, most preferably 5mJ / cm 2 Above 30mJ / cm 2 When the accumulated light intensity is reduced, the expansion of the cured film in the in-plane direction becomes smaller. When the accumulated light intensity is increased, the surface state of the coating film deteriorates.

[0096] After the first irradiation step is completed, the second irradiation step is performed. In the second irradiation step, the coating film is irradiated with the second radiation to cure the entire coating film. Thus, the surface protection layer 5 is obtained.

[0097] The second radiation is ionizing radiation such as electron beams, or ultraviolet light having a longer wavelength than the first radiation. When ultraviolet light is used as the second radiation, the ultraviolet light has a wavelength at which the ionizing radiation curable resin exhibits a smaller absorption coefficient.

[0098] The integrated light intensity of the second radiation is preferably set to 10 mJ / cm 2 Above 500mJ / cm 2 Below, more preferably 50 mJ / cm 2 Above 400mJ / cm 2 Below, more preferably 100 mJ / cm 2 Above 300mJ / cm 2the following.

[0099] The decorative sheet 1 can be manufactured, for example, by the above method. The decorative sheet 1 can also be manufactured by other methods. For example, the surface protection layer 5 can be formed by forming a plate using the above method and transferring using the plate to form a surface protection layer 5 having a concavo-convex structure on the surface.

[0100] <3> Effect

[0101] Reference Figures 1 to 3 The surface protection layer 5 of the decorative sheet 1 described has the above-mentioned surface properties. Such a decorative sheet 1 gives a wet touch feeling to the user when the user slides the finger on the surface while pressing the surface of the surface protection layer 5 with the skin, for example, when the user slides the finger on the surface while pressing the surface of the surface protection layer 5 with the finger. That is, since the slope of the concave-convex shape on the surface of the decorative sheet 1 located on the surface of the surface protection layer 5 is relatively gentle, when touching by the above-mentioned action, the pressure resistance caused by the contact between the finger and the surface can be suppressed to a small level, and the contact area between the finger and the convex surface can be gradually increased. As a result, the touch feeling of the surface of the decorative sheet adsorbed on the finger can be obtained.

[0102] The moist touch can make the person who touches the decorative sheet 1 feel comfortable and warm. In addition, the moist touch can give a sense of luxury to the decorative sheet 1. Therefore, the decorative sheet 1 that gives the user a moist touch is suitable for applications that have many opportunities to contact the user's skin or applications that contact the user's skin for a long time, such as tabletops, chair armrests, and railings of stairs or passages.

[0103] Since the surface protection layer 5 of the decorative sheet 1 has the above-mentioned surface properties, low gloss can be achieved even without a gloss regulator (matting additive). The gloss regulator reduces the oleophobicity of the layer formed by the resin material, so the surface protection layer 5 containing the gloss regulator is easy to be attached with fingerprints. The surface protection layer 5 without the gloss regulator is difficult to absorb oil, so fingerprints are difficult to be attached. In addition, the surface protection layer 5 with excellent oleophobicity is difficult to adsorb oil or pollutants. In addition, when the surface of the surface protection layer 5 without the gloss regulator is scratched, the particles of the gloss regulator will not fall off, so the decorative sheet 1 including such a surface protection layer 5 is difficult to produce gloss changes and scratches.

[0104] The reason why the surface protection layer 5 having the above-mentioned surface properties can be obtained by the above-mentioned method is as follows.

[0105] Oxygen in the gas phase not only absorbs short-wavelength ultraviolet rays, but also hinders free radical polymerization. The effect of oxygen contained in the gas phase on free radical polymerization is greatest in the portion adjacent to the gas phase in the coating film composed of ionizing radiation curable resin, and becomes smaller as the distance from the coating film surface increases. Therefore, in the first irradiation step, by changing the oxygen concentration in the gas phase, the relationship between the distance from the coating film surface and the degree of progress of the crosslinking reaction can be changed.

[0106] When this relationship changes, the thickness of the cured film produced on the surface of the coating film by the first irradiation process and the expansion degree of the cured film in the in-plane direction based on the cross-linking reaction change. The accumulated light amount of the first irradiation process will also affect the thickness of the cured film and the expansion degree of the cured film in the in-plane direction. Moreover, the thickness of the cured film and the expansion degree of the cured film in the in-plane direction will affect the surface properties of the surface protective layer. In addition, the particle size and addition amount of the particles in the coating film and the thickness of the coating film will also affect the formation of wrinkles.

[0107] Therefore, for example, by appropriately setting the composition of the ionizing radiation curable resin, the particle size and addition amount of the particles, the thickness of the coating, the oxygen concentration in the gas phase of the first irradiation step, and the accumulated light amount of the first irradiation step, a surface protective layer having the desired surface properties can be obtained.

[0108] Example

[0109] Hereinafter, examples of the present invention will be described.

[0110] <Example 1>

[0111] The reference was created by Figures 1 to 3 The decorative sheet 1 is described. It should be noted that in this example, the transparent resin layer 4, the primer layer 6, the adhesive layer 7 and the concealing layer 8 are omitted.

[0112] First, prepare a unit area mass of 50g / m 2 As the raw material layer 2, an impregnated paper (GFR-506: manufactured by Kojin Co., Ltd.) was used. On one surface of the raw material layer 2, a pattern layer 3 was formed using an oily nitrocellulose resin-based gravure printing ink (PCNT (PCRNT) various colors: manufactured by Toyo Ink Co., Ltd.).

[0113] Next, a coating liquid for a surface protective layer is applied onto the pattern layer 3. As the coating liquid for a surface protective layer, a coating liquid prepared by blending the following particles into the following ionizing radiation curable resin is used.

[0114] ·Ionizing radiation curable resin

[0115] Type: Trimethylolpropane EO modified triacrylate (EO15 molar addition)

[0116] Product name: SR9035 (Sartomer)

[0117] Mixing: 100 parts by mass

[0118] ·particle

[0119] Product name: SYLYSIA 250N (manufactured by Fuji Silysia Chemical Ltd.)

[0120] Particle size: 5μm

[0121] Mixing: 5 parts by mass

[0122] A coating film composed of the surface protective layer coating liquid was formed to have a thickness of 5 μm.

[0123] Then, the first irradiation step was performed. Specifically, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 500 ppm under atmospheric pressure so that the accumulated light intensity was 50 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating liquid was irradiated with ultraviolet rays having a wavelength of 172 nm. As a result, wrinkles were generated on the surface of the coating film.

[0124] Next, the second irradiation step is performed. Specifically, the coating film is irradiated with ionizing radiation to cure the entire coating film, thereby forming the surface protection layer 5.

[0125] The decorative sheet 1 was obtained through the above-mentioned process.

[0126] <Comparative Example 1>

[0127] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, no particles were blended.

[0128] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0129] <Comparative Example 2>

[0130] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 2 parts by mass.

[0131] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 90 mJ / cm 2The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0132] <Example 2>

[0133] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 3 parts by mass.

[0134] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 250 ppm under atmospheric pressure so that the accumulated light intensity was 70 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0135] <Example 3>

[0136] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 4 parts by mass.

[0137] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 400 ppm under atmospheric pressure so that the accumulated light intensity was 60 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0138] <Example 4>

[0139] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 10 parts by mass.

[0140] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 750 ppm under atmospheric pressure so that the accumulated light intensity was 40 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0141] <Example 5>

[0142] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 11 parts by mass.

[0143] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 750 ppm under atmospheric pressure so that the accumulated light intensity was 40 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0144] <Comparative Example 3>

[0145] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 12 parts by mass.

[0146] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 750 ppm under atmospheric pressure so that the accumulated light intensity was 40 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0147] <Comparative Example 4>

[0148] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, a coating film composed of the surface protective layer coating liquid was formed to have a thickness of 1 μm.

[0149] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0150] <Example 6>

[0151] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, a coating film composed of the surface protective layer coating liquid was formed to have a thickness of 2 μm.

[0152] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 80 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0153] <Example 7>

[0154] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, a coating film composed of the surface protective layer coating liquid was formed to have a thickness of 3 μm.

[0155] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 200 ppm under atmospheric pressure so that the accumulated light intensity was 70 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0156] <Example 8>

[0157] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, a coating film composed of the surface protective layer coating liquid was formed to have a thickness of 10 μm.

[0158] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 700 ppm under atmospheric pressure so that the accumulated light intensity was 20 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0159] <Example 9>

[0160] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, a coating film composed of the surface protective layer coating liquid was formed to have a thickness of 18 μm.

[0161] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 700 ppm under atmospheric pressure so that the accumulated light intensity was 10 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0162] <Comparative Example 5>

[0163] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, a coating film composed of the surface protective layer coating liquid was formed to have a thickness of 20 μm.

[0164] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 700 ppm under atmospheric pressure so that the accumulated light intensity was 5 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0165] <Comparative Example 6>

[0166] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0167] ·particle

[0168] Product name: SYLYSIA 310P (manufactured by Fuji Silysia Chemical, Ltd.)

[0169] Particle size: 2μm

[0170] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 600 ppm under atmospheric pressure so that the accumulated light intensity was 40 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0171] <Example 10>

[0172] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0173] ·particle

[0174] Product name: SYLYSIA 420 (manufactured by Fuji Silysia Chemical, Ltd.)

[0175] Particle size: 3μm

[0176] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 550 ppm under atmospheric pressure so that the accumulated light intensity was 45 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0177] <Example 11>

[0178] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0179] ·particle

[0180] Product name: SYLYSIA 430 (manufactured by Fuji Silysia Chemical, Ltd.)

[0181] Particle size: 4 μm

[0182] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 550 ppm under atmospheric pressure so that the accumulated light intensity was 45 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0183] <Example 12>

[0184] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0185] ·particle

[0186] Product name: SYLYSIA 450 (manufactured by Fuji Silysia Chemical, Ltd.)

[0187] Particle size: 8μm

[0188] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 400 ppm under atmospheric pressure so that the accumulated light intensity was 80 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0189] <Example 13>

[0190] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0191] ·particle

[0192] Trade name: SYLYSIA 882 (manufactured by Fuji Silysia Chemical, Ltd.)

[0193] Particle size: 10 μm

[0194] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0195] <Example 14>

[0196] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0197] ·particle

[0198] Product name: SYLYSIA 780 (manufactured by Fuji Silysia Chemical, Ltd.)

[0199] Particle size: 11 μm

[0200] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0201] <Example 15>

[0202] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following particles were used.

[0203] ·particle

[0204] Product name: Sicastar 43-00-154 (manufactured by COREFRONT Corporation)

[0205] Particle size: 14 μm

[0206] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0207] <Comparative Example 7>

[0208] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0209] ·Ionizing radiation curable resin

[0210] Type: Trimethylolpropane triacrylate

[0211] Product name: NK ESTER A-TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0212] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0213] <Example 16>

[0214] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0215] ·Ionizing radiation curable resin

[0216] Type: Trimethylolpropane EO modified triacrylate (EO3 molar addition)

[0217] Product name: Miramer M3130 (made by Miwon)

[0218] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0219] <Example 17>

[0220] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0221] ·Ionizing radiation curable resin

[0222] Type: Trimethylolpropane EO modified triacrylate (EO6 molar addition)

[0223] Product name: Miramer M3160 (made by Miwon)

[0224] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0225] <Example 18>

[0226] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0227] ·Ionizing radiation curable resin

[0228] Type: Trimethylolpropane EO modified triacrylate (EO9 molar addition)

[0229] Product name: SR502 (manufactured by Sartomer Company)

[0230] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 200 ppm under atmospheric pressure so that the accumulated light intensity was 80 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0231] <Example 19>

[0232] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0233] ·Ionizing radiation curable resin

[0234] Type: Trimethylolpropane EO modified triacrylate (EO20 molar addition)

[0235] Product name: NK ESTER AT-20E (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0236] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 600 ppm under atmospheric pressure so that the accumulated light intensity was 45 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0237] <Example 20>

[0238] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0239] ·Ionizing radiation curable resin

[0240] Type: Ethoxylated pentaerythritol tetraacrylate (EO20 molar addition)

[0241] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 600 ppm under atmospheric pressure so that the accumulated light intensity was 45 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0242] <Example 21>

[0243] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0244] ·Ionizing radiation curable resin

[0245] Type: Ethoxylated pentaerythritol tetraacrylate (EO35 molar addition)

[0246] Product name: NK ESTER ATM-35E (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0247] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 650 ppm under atmospheric pressure so that the accumulated light intensity was 40 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0248] <Comparative Example 8>

[0249] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the compounding amount of the particles was set to 15 parts by mass.

[0250] Then, the coating film composed of the surface protection layer coating liquid is cured only by the second irradiation step without performing the first irradiation step.

[0251] <Comparative Example 9>

[0252] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0253] ·Ionizing radiation curable resin

[0254] Type: Ethylene glycol diacrylate (EO9 molar addition)

[0255] Product name: Light Acrylate 9EG-A (manufactured by Kyoeisha Chemical Co., Ltd.)

[0256] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 550 ppm under atmospheric pressure so that the accumulated light intensity was 40 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0257] <Comparative Example 10>

[0258] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0259] ·Ionizing radiation curable resin

[0260] Type: Ethoxylated dipentaerythritol hexaacrylate (EO12 molar addition)

[0261] Product name: NK ESTER A-DPH-12E (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0262] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0263] <Comparative Example 11>

[0264] The decorative sheet 1 was produced by the same method as in Example 1 except for the following points. That is, in this example, the following ionizing radiation curable resin was used.

[0265] ·Ionizing radiation curable resin

[0266] Type: Pentaerythritol tetraacrylate

[0267] Product name: NK ESTER A-TMMT (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0268] In the first irradiation step, a Xe excimer lamp was used in a nitrogen atmosphere with an oxygen concentration of 100 ppm under atmospheric pressure so that the accumulated light intensity was 100 mJ / cm 2 The surface of the coating film composed of the surface protective layer coating solution was irradiated with ultraviolet rays having a wavelength of 172 nm.

[0269] <Evaluation>

[0270] The following evaluations were performed on each of the decorative sheets.

[0271] (1) Thickness of surface protective layer

[0272] The thickness of the surface protective layer is measured as follows. After the decorative sheet 1 is embedded in a resin such as a cold-curing epoxy resin or a UV-curable resin and fully cured, it is cut to make the cross-section of the decorative sheet 1 appear, and mechanical grinding is performed to obtain a measurement surface. Next, the thickness of the surface protective layer is measured using a scanning electron microscope SIGMA 500 manufactured by Carl Zeiss Microscopy GmbH. Any 25 points are measured, and the measured value after averaging the 25 points is defined as the "thickness t of the surface protective layer". The measurement implementation conditions are set to: an acceleration voltage of 0.5 keV (low acceleration voltage), a photographic mode of SE2 mode, and a magnification of 2000 times. The measurement sample was not sputtered. The "thickness t of the surface protective layer" is equal to the thickness of the coating film composed of the coating liquid for the surface protective layer.

[0273] (2) Glossiness

[0274] Glossiness The 60-degree glossiness was measured using Rhopoint IQ (manufactured by Konica Minolta, Inc.) The “60-degree glossiness value” in Tables 1 to 4 below indicates the 60-degree glossiness.

[0275] (3) Skin touch

[0276] Skin feel was evaluated by the following method.

[0277] First, in order to make the evaluation criteria consistent among the evaluators, we conducted preliminary preparations. Specifically, we prepared three standard test pieces with different surface properties. Then, we asked the five evaluators to press the surface of the standard test piece with their fingers while sliding their fingers on the surface while blindfolded, and then divided the touch into the following three groups.

[0278] Group 1: Although almost no push-in resistance was felt, the surface of the decorative sheet felt like it was adsorbed on the finger, and a good sliding feeling was felt, and the impression of a good sliding feeling was enhanced as a whole. In other words, a smooth feeling was felt.

[0279] Group 2: Although almost no resistance to pushing in was felt, the surface of the decorative sheet felt like it was being sucked by the finger. However, there was no impression of a smooth sliding feeling. In other words, a wet feeling was felt.

[0280] Group 3: They felt the resistance to pushing in and the presence of the bumps and depressions. That is, they felt a rough touch.

[0281] Repeat the above steps until the evaluations of each evaluator are consistent for more than 3 consecutive times, and the evaluation results between evaluators are consistent for 3 consecutive times.

[0282] Next, for each of the decorative sheets, the evaluators were asked to slide their fingers over the surface while pressing the surface of the surface protection layer with their fingers while blindfolded, and then the touch was classified into the above three groups. This step was then repeated until the evaluations of each evaluator were consistent for three or more consecutive times, and the evaluation results of the evaluators were consistent for three consecutive times. Based on the results, the skin touch was evaluated according to the following criteria.

[0283] A (smooth): Group 1

[0284] B (wet): Group 2

[0285] C (rough): Group 3

[0286] (4) Fingerprint resistance

[0287] As the anti-fingerprint evaluation, the fingerprint wiping property evaluation was performed.

[0288] Specifically, the 60-degree glossiness of the surface of each decorative sheet was first measured, and the 60-degree glossiness was taken as the initial glossiness. Next, an anti-fingerprint evaluation liquid was attached to the surface protective layer, and the anti-fingerprint evaluation liquid attached to the surface of the decorative sheet was wiped off. Here, a higher fatty acid was used as the anti-fingerprint evaluation liquid. Then, the 60-degree glossiness of the portion after wiping the anti-fingerprint evaluation liquid was measured, and the 60-degree glossiness was taken as the glossiness after wiping.

[0289] The fingerprint wipe rate is calculated according to the following formula.

[0290] Fingerprint wiping rate (%) = (gloss after wiping / initial gloss) × 100

[0291] The evaluation criteria are as follows.

[0292] AA: 70% or more and less than 250%

[0293] A: 50% or more and less than 70%, or 250% or more and less than 300%

[0294] B: less than 50%, or more than 300%

[0295] (5)Pollution resistance

[0296] As an evaluation of stain resistance, a stain test A specified in Japanese Agricultural Standards (JAS) was performed. That is, a line with a width of 10 mm was drawn on the surface protective layer of each decorative sheet using blue ink, black quick-drying ink, and red crayon, respectively, and left for 4 hours. Then, the lines of blue ink, black quick-drying ink, and red crayon were wiped with a cloth containing ethanol.

[0297] The evaluation criteria are as follows.

[0298] AA: Each color thread can be wiped easily.

[0299] A: You can wipe part of each color thread, but dirt will remain on some of it.

[0300] B: The colored threads cannot be wiped off.

[0301] (6) Damage resistance

[0302] Each decorative sheet was attached to the wooden substrate B using a urethane adhesive. Then, a stainless steel wool friction test was performed as a scratch resistance evaluation. Specifically, the decorative sheet was rubbed back and forth 20 times with stainless steel wool while applying a load of 100 g, and the scratches and gloss changes on the surface of the decorative sheet were visually confirmed.

[0303] The evaluation criteria are as follows.

[0304] AA: No surface damage or gloss change

[0305] A: Slight damage or gloss change on the surface

[0306] B: The surface has obvious damage or gloss changes

[0307] (7) Processability

[0308] The obtained decorative sheet was adhered to the wooden substrate B using a urethane adhesive in such a manner that the surface on the raw material layer side (i.e., the back side of the decorative sheet) faced the wooden substrate B. Then, a V-shaped groove was placed at the boundary where the wooden substrate B and the decorative sheet were adhered in such a manner as not to damage the decorative sheet.

[0309] Next, the wood substrate B was bent 90 degrees along the V-shaped groove so that the surface of the decorative sheet on the surface protection layer side (i.e., the surface of the decorative sheet) was folded. The bending workability was evaluated by observing the bent portion of the surface of the decorative sheet using an optical microscope to see whether whitening or cracking occurred.

[0310] The evaluation criteria are as follows.

[0311] AA: No whitening or cracking observed

[0312] A: Some bleaching was observed

[0313] B: Whitening is observed on the entire surface or cracks are observed on a part of the surface

[0314] (8) Section height difference Rdc and ratio Rdc / t

[0315] The cross-sectional height difference Rdc (μm) and the ratio Rdc / t are obtained as described in detail above.

[0316] The evaluation results are shown in Tables 1 to 4. In Tables 1 to 4, when the evaluation result of the skin touch is A (smooth), it is indicated by filling in the character Y in the "A (smooth)" column; when the evaluation result of the skin touch is B (moist), it is indicated by filling in the character Y in the "B (moist)" column; when the evaluation result of the skin touch is C (rough), it is indicated by filling in the character Y in the "C (rough)" column.

[0317] [Table 1]

[0318]

[0319] [Table 2]

[0320]

[0321] [Table 3]

[0322]

[0323] [Table 4]

[0324]

[0325] As shown in Tables 1 to 4, the decorative sheets of Examples 1 to 21 gave the evaluators a moist touch. In addition, the decorative sheets of Examples 1 to 21 had low gloss and excellent fingerprint resistance, stain resistance and processability. In addition, the decorative sheets of Examples 1 to 14 and 16 to 21 also had excellent scratch resistance.

[0326] As shown in Table 1, Comparative Example 3 gave the evaluator a wet touch and had low gloss, but was poor in stain resistance, scratch resistance, and processability. As shown in Table 4, Comparative Example 8 gave the evaluator a wet touch, but had high gloss, and was poor in fingerprint resistance, stain resistance, and scratch resistance.

[0327] In contrast, as shown in Tables 1, 2, and 4, Comparative Examples 1, 2, 5, 6, and 9 did not give the evaluators a wet touch, but a rough touch. Also, as shown in Tables 2 to 4, Comparative Examples 4, 7, 10, and 11 did not give the evaluators a wet touch, but a smooth touch.

[0328] Explanation of symbols

[0329] 1…decorative sheet, 2…raw material layer, 3…pattern layer, 4…transparent resin layer, 5…surface protection layer, 6…primer layer, 7…adhesive layer, 8…hidden layer, 11…decorative material, B…substrate.

Claims

1. A decorative sheet comprising a raw material layer and a surface protection layer provided on one surface of the raw material layer, A concavo-convex structure including a plurality of ridge-shaped portions each protruding in a ridge shape is provided on the surface of the surface protection layer. A ratio Rdc / t of a cross-sectional height difference Rdc of the concavo-convex structure of the surface protection layer to a thickness t of the surface protection layer is 0.1 or more and 0.2 or less, The thickness t of the surface protection layer is not less than 2 μm and not more than 18 μm, The surface protective layer contains a cured product of a resin and particles, the particles have an average particle diameter of 3 μm or more, and the particles are contained in the surface protective layer in an amount of 3 parts by mass or more and 11 parts by mass or less relative to 100 parts by mass of the resin, The glossiness of the surface protection layer is less than 10.

2. The decorative sheet according to claim 1, wherein: The average particle size of the particles is not less than 3 μm and not more than 11 μm.

3. The decorative sheet according to claim 1 or 2, wherein: The resin is an ionizing radiation curable resin.

4. The decorative sheet according to any one of claims 1 to 3, wherein: The resin is acrylate.

5. The decorative sheet according to any one of claims 1 to 4, wherein: The resin is a trifunctional acrylate including a repeating structure, and the repeating number of the repeating structure is 3 or more and 20 or less.

6. The decorative sheet according to any one of claims 1 to 4, wherein: The resin is a tetrafunctional acrylate including a repeating structure, and the repeating number of the repeating structure is 20 or more and 35 or less.

7. The decorative sheet according to any one of claims 1 to 6, wherein: A pattern layer is further provided between the raw material layer and the surface protection layer.

8. A decorative material having: A decorative sheet according to any one of claims 1 to 7, and a substrate to which the decorative sheet is attached.

Citation Information

Patent Citations

  • Decorative material

    JP2019119138A

  • Decorative sheet

    JP2021165033A